Organic Cation Engineering for Vertical Charge Transport in Lead‐Free Perovskite Quantum Wells. Issue 8 (7th February 2021) - Ma, Ke; Hsu, Sheng-Ning; Gao, Yao; Wei, Zitang; Jin, Linrui; Finkenauer, Blake P.; Huang, Libai; Boudouris, Bryan W.; Mei, Jianguo; Dou, Letian
Abstract : 2D organic–inorganic hybrid halide perovskites are promising semiconductor materials for a variety of device applications. However, fundamental issues of charge transport through multiple quantum wells separated by bulky organic ligands remain unsolved. Herein, a mixture of π‐conjugated organic ligands, (2‐(3‴, 4′‐dimethyl‐[2, 2′:5′, 2′:5″, 2‴‐quaterthiophen]‐5‐yl)ethan‐1‐ammonium iodide) (4Tm) and 2‐([2, 2′‐bithiophen]‐5‐yl)ethan‐1‐aminium iodide (2T), is used as spacer to form (4Tm) x (2T)2− x SnI4 2D perovskite thin films. The new strategy of alloying 2T into 4Tm ligands reduces the interlayer distance (barrier thickness) while maintaining the relatively small energy barrier height for the hybrid quantum wells, enhances interlayer interactions, and improves charge transport across adjacent perovskite layers. Moreover, solar cell devices fabricated with (4Tm) x (2T)2− x SnI4 exhibit improved photovoltaic properties and stability. Abstract : 2D organic–inorganic hybrid halide perovskites improve the stability of perovskite photovoltaic devices, but suffer from inefficient charge transfer through multiple quantum wells. Alloyed π‐conjugated organic ligands are used as spacers to shorten the interlayer distances and lower energy barrier heights simultaneously to achieve promising optoelectronic properties. The conjugated ligands also improve the stability of the fabricated devices.